Identification of ISSR-based Molecular Markers Associated with Ploidy Level of Orange Watermelon (Citrullus lanatus (Thunb.) Matsum & Nakai) - Andra Jausa Salsabila; Budi Setiadi Daryono; Aprilia Sufi Subiastuti (Universitas Gadjah Mada, 2021)
Indonesia is an agrarian country whose territory is partly used as an agricultural sector, has especially watermelon (Citrullus lanatus (Thunb.) Matsum & Nakai). At present, the development of watermelons in Indonesia still requires a variety of colors, superior watermelons need to be developed by making triploid orange watermelons. The new watermelon cultivar (F₁) is the result of crossing 'Jelita' (♀) and 'BallyBall' (♂) which are expected to provide a combination of characters that can produce large and sweet fruits. The purpose of this study was to identify ISSR markers that were associated with ploidy levels of horticultural crops, particularly watermelon. The watermelons were growns on the agricultural land of Kebondalem Hamlet, Madurejo Village, Prambanan District, D.I.Y. and analyzed at the Laboratory of Biotechnology PAU, UGM and Laboratory of Genetics and Breeding, Faculty of Biology UGM. Analysis of genetic variation was carried out using the PCR-ISSR method and the DNA bandwidth was calculated using Paint Apps, Microsoft Excel 2013, and Microsoft Word 2013. The results of crossing 'Jelita' and 'King Quality 'is sterile. The result of 'Jelita' with 'BallyBall' produces tillers until sterile harvest time. The results of the analysis of genetic variation using the PCR-ISSR method indicate that the ISSR BI, B3, B5, and CBTC 1 molecular markers cannot be used to distinguish ploidy from the tested watermelons.